Trade Unionism in French-Speaking West Africa: From the Supervising Metropolitan Headquarters to Supervising Political Parties: The Difficult Search for an Identity (1900–1968) - (:unkn) unknown (My University, 2006)
Introduced in a colonial context, the trade-unions of French West Africa first emerged as a result of exchanges between migrants, particularly seamen, influenced by the CGT. Their development was, however, for a long time constrained by the local absence of the right of association. The history of the AOF labour movement is characterised by some long strikes (in the field of railway transport particularly), marked by racial tensions but also by co-operation between Europeans and Africans. After the Second World War, the African tradeunions become extensions of the main French trade-unions before attempting to find their autonomy. This highlights the paradox of internationalism in a colonial context. A double rupture, firstly with the French working class, which was denounced by the CGT, and then with the international federations, accompanied the creation in 1957 of the UGTAN (General Union of the African Workers). This was a transnational organisation that went on to fight against the ruling parties of the newly independent single-party states.
Keywords: African Research